Evidences for multiple maternal lineages of Caryocar brasiliense populations in the Brazilian Cerrado based on the analysis of chloroplast DNA sequences and microsatellite haplotype variation - Collevatti, Rosane G.; Grattapaglia, Dario; Hay, JOHN. D. (Molecular ecology, 2003)
In this work we report on the phylogeography of the endangered tree species Caryocar brasiliense based on variability in two classes of maternally inherited chloroplast DNA sequences with different rates of molecular evolution. Eleven sequence haplotypes of a noncoding region between the genes trnT and trnF and 21 distinct 10‐locus microsatellite haplotypes could be identified in a total of 160 individuals, collected in 10 widespread populations of C. brasiliense. An amova indicated that most of the variation can be attributed to differences among populations, both for DNA sequence (87.51%) and microsatellites (84.38%). Phylogeography based on a median‐joining network analysis of the noncoding region showed a sharp difference from the analysis of microsatellite haplotypes. Nevertheless, both analyses indicated that multiple lineages may have contributed to the origin of C. brasiliense populations in Brazilian Cerrado. Incongruences in the microsatellite haplotypes network suggest that homoplasy, which emerged from recurrent and independent mutations, greatly influenced the evolution of the C. brasiliense chloroplast genome. We hypothesize that our results may show the outcome of the restriction of ancient relic populations to moist refugias during extended droughts coinciding with glaciation in the northern hemisphere. The subsequent spread to favourable areas throughout Central Brazil may have caused contact between different lineages during the interglacial periods. The extinction of megafauna dispersers in the last glaciation may have caused a restriction in seed movement and currently, gene flow has been occurring mainly by pollen movement.